MENSAGEM DOS DIRIGENTES - Friede, Reis; Azulay Neto, Messod; Araújo Filho, Luiz Paulo da Silva; Athié, Ivan (LexCult: revista eletrônica de direito e humanidades; v. 4 n. 1 (2020): Estado em DebateDO - 10.30749/2594-8261.v4n1p12-13, 2020)
Mensagem dos Dirigentes.